Structuring Geography Lessons with the Help of Geographical Concepts: Ein international erfolgreicher Weg zur Erlangung fachlicher Identität und gesellschaftlicher Relevanz - Uhlenwinkel, Anke (Journal of Geography Education, 2013)
Geographical concepts are a well-known tool for curriculum making in Britain as well as in France. This paper argues that they would also be helpful to overcome the lasting dichotomy between thematic and regional approaches in the curricula of the German federal states. To validate this view each geographical concept is theoretically explained. Its practical value is then demonstrated using Israel as an example. While this discussion draws heavily on British and French resources, the paper then turns to the German context and examines the concepts in relation to the spatial concepts used in the Educational Standards. From here the argument leads to practical proposals for a convergence of thematic and regional approaches in geography teaching. Finally the concepts are discussed in the relation to educational debates on constructivism, spatial thinking, cross-curricular approaches and competences.